Relatively low plasma cortisol levels in parturients are associated with epidural-related maternal fever - Chenxi Zhang; Qinjun Chu; Tao Wang; Hailong Bing; Lihui Bai; Liwei Sun; Dongqing Zhang; Jie Wang; Li Li; Qin Zhou; Zhengyuan Xia; Xiaogao Jin (Annals of Medicine, 2025)
Background Epidural analgesia (EA) may suppress the stress response or cortisol production during vaginal delivery by blocking pain transmission. However, there is no evidence that epidural analgesia contributes to epidural-related maternal fever (ERMF) by inhibiting the hypothalamic pituitary adrenal (HPA) axis.Objective This study aimed to evaluate the relationship between maternal cortisol levels and ERMF during vaginal delivery.Study design Prospective cohort study.Methods The venous blood samples were collected from full-term pregnant women undergoing vaginal delivery and categorized into control group (<37.5 °C without EA), normal group (<37.5 °C with EA), mild group (37.5–37.9 °C with EA) or fever group (≥38 °C with Epidural analgesia (EA)). Then, plasma cortisol and pro-inflammatory cytokine levels (IL-6, TNF-α, IL-2 and IFN-γ) were assessed to determine the impact of EA on the stress response. We also detected hormones related to the HPA axis, including CRH and ACTH plasma concentration. Additionally, general adrenal function was evaluated by measuring renin, aldosterone, testosterone, and DHEA-s concentrations in the maternal venous blood. Clinical evidence of adrenal dysfunction was also investigated using medical records.Results Epidural analgesia induced high levels of cytokines IL-6 and TNF-α in all parturients, but ERMF was observed only in those with lower cortisol levels. Correlation analysis revealed a positive relationship between IL-6 (or TNF-α) and cortisol concentration ratio and maximum maternal temperature. Elevated ACTH, β-endorphin and αMSH levels were observed in parturients with ERMF, indicating primary adrenal dysfunction. Medical records showed no significant differences in symptoms, signs, or laboratory results related to adrenal function among the four groups.Conclusion There was a relationship between relatively low maternal cortisol levels and ERMF.Trial registration number ChiCTR2200058359 obtained on April 7, 2022.